Carbon Tax Policy Analysis of Negative Emission Externalities in South Sulawesi (Case Study at PT. Makassar Industrial Estate) - Muh Asrullah Arifin; Asriani Junaid; Amiruddin Amiruddin (Jurnal Riset Perpajakan: Amnesty, 2025)
This research aims to analyze the implementation of carbon tax policy on negative emission externalities in South Sulawesi, with a case study of PT. Kawasan Industri Makassar (PT. KIMA). This study employs a qualitative approach, based on the type of data collected. Informants include the Head of the Clean Water and Waste Department, staff from the Environmental Monitoring and Reporting Division, and the division’s administrative personnel at PT. KIMA. The findings reveal that PT. KIMA, an industrial sector company responsible for managing industrial zones, contributes to carbon emissions through two main sources: incinerator operations and external industrial activities within the area. However, the company has not yet implemented any formal carbon tax mechanisms to mitigate emissions. This is primarily due to the absence of technical guidelines or regulatory directives related to carbon tax implementation for industrial area management companies. Despite the lack of a carbon tax policy, PT. KIMA has made environmental efforts by promoting green initiatives, such as developing green open spaces (Ruang Terbuka Hijau/RTH) and tree planting along industrial area roads to help absorb carbon emissions and reduce environmental impact.